Should tumor with direct adjacent lobe invasion (Tdali) be assigned to T2 or T3 in non-small cell lung cancer: a meta-analysis - Xiao, Zhilan; Cao, Christphor; Mei, Jiandong; Liao, Hu; Yan, Tristan; Liu, Lunxu (Journal of Thoracic Disease, 2016)
Background: The staging of tumor with direct adjacent lobe invasion (Tdali) or interlobar invasion pleural 3 (ILI PL3) in TNM system of non-small cell lung cancer (NSCLC) is still in controversy. We conducted a meta-analysis to compare the prognosis of Tdali with T2 or T3 disease. Methods: PubMed and Embase were searched for relevant studies. Ln hazard ratio (HR) and its standard error (SE) of each study were estimated in the comparison of overall survival (OS) between Tdali and T2 or T3 respectively. Forest plots were used to show the combined HRs. Results: The meta-analysis for comparison of OS of Tdali and T2 or T3 disease both showed a significant HR [Tdali versus T2, 1.39 (1.21, 1.61), P